Study of the Impact of Sustainability Trends in Business After Pandemic - Elena Florentina GREJDAN; Elena GOGA; Iasmina-Iulia GRĂDINESCU; Gheorghe ORZAN; Cristina NICOLAE; Bianca Cristiana VOICU; Ionuț TĂNASE (Communications of International Proceedings, 2022)
During the past two years, we all have faced the COVID-19 pandemic. In national defense perspective, COVID-19 pandemic could be viewed as a non-military threat to national defense. The COVID-19 pandemic is a wake-up call that improves our awareness on the necessity to be fully independent and self-sufficient. A new outbreak of virus has influenced almost everything, partially or completely changing the normal life. It forced to introduce new approaches or to take actions to lessen the impact and to bring its to minimum. The influence did not pass by businesses, but dramatically changed them. The scope of the present paper is to reveal that the impact of the companies is organized around the purpose of positive impact, which we define as increasing economic prosperity while contributing to a healthy environment and improving human wellbeing. The research method involves a quantitative investigation with an exploratory-descriptive scope. The sample consisted of 300 participants of the business field. Compared to other articles that have analyzed this idea, our main objectives were to analyse the tendency of entrepreneurs to implement new sustainability strategies, if they predicted the tendency of the entrepreneurial environment to invest in sustainability marketing strategies.
Keywords: pandemic; COVID-19; industries; entrepreneurs; business; impact; world; economy; sustainability